2016
DOI: 10.1074/jbc.m116.739169
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model for Dietary Xenosialitis

Abstract: Humans can incorporate the xenoglycan N-glycolylneuraminic acid (Neu5Gc) from the diet into reproductive tissues and secretions. Most humans also have circulating antibodies specific for this dietary xenoglycan. The potential for inflammation induced by incorporated Neu5Gc and circulating anti-Neu5Gc antibodies, termed xenosialitis, has been discussed as a factor influencing several human diseases. Potential effects of xenosialitis on human fertility remain unknown. Here, we investigate possible adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Mammals make anti-sperm antibodies when directly exposed to sperm (72). Major human sperm antigens include, highly sialylated GPI-anchored glycoproteins such as CD52 (73, 74), which in males that have a functional CMAH allele, carry Neu5Gc (75). Theoretically, immunization of females homozygous for the loss-of-function allele of Cmah could occur via insemination by males that have Neu5Gc-bearing sperm.…”
Section: Evolutionary Mechanisms For the Fixation Of Loss-of-functionmentioning
confidence: 99%
“…Mammals make anti-sperm antibodies when directly exposed to sperm (72). Major human sperm antigens include, highly sialylated GPI-anchored glycoproteins such as CD52 (73, 74), which in males that have a functional CMAH allele, carry Neu5Gc (75). Theoretically, immunization of females homozygous for the loss-of-function allele of Cmah could occur via insemination by males that have Neu5Gc-bearing sperm.…”
Section: Evolutionary Mechanisms For the Fixation Of Loss-of-functionmentioning
confidence: 99%
“…We hypothesize that sperm sialic acids and female-expressed Siglecs may modulate the leukocytic reaction and promote sperm survival within the female reproductive tract. Indeed, a recent report has shown that sialic acids on sperm are protective against phagocytosis by macrophages, ex vivo (25). To begin to address this, we investigated sialic acid-dependent interactions between sperm and isolated neutrophils in vitro.…”
mentioning
confidence: 99%
“…This mechanism was demonstrated in human-like Cmah null mice (44, 46). On the other hand, a random CMAH mutation may simply have become fixed in a small group of individuals who eventually gave rise to modern humans.…”
Section: Humans Cannot Synthesize Neu5gcmentioning
confidence: 81%